STUDI KELAYAKAN BISNIS DITINJAU DARI ASPEK INDUSTRI DAN KEUANGAN PADA PENGEMBANGAN USAHA HARNESS HEWAN ERGONOMIS (BIRKINPET) - ANITA hakim nasution (Institut Teknologi Adhi Tama Surabaya, 2026)
This research aims to evaluate the business feasibility of ergonomic harness hewanes in Indonesia from the perspectives of market potential, product value, and financial viability. As pet ownership continues to rise in Indonesia, harness products have become essential for pet owners who emphasize safety and comfort. The study applies capital budgeting techniques—specifically Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP)—to determine financial feasibility. To achieve returns exceeding the Minimum Attractive Rate of Return (MARR) of 13%, the business must reach a minimum annual sales volume of 2,119 units, priced at Rp211,125 each, with an annual sales growth rate of 10%. BirkinPet’s target of 2,200 units per year indicates that the plan is financially viable, supported by a projected NPV of Rp72,175,425, an IRR of 32%, and a payback period achieved in the fifth year. The findings conclude that the business is feasible, as sales projections surpass the minimum threshold. The study further recommends expanding market reach through digital marketing initiatives and continuous product innovation.